Quality Improvement of X Brand Tube Packaging PT XYZ Using the Six Sigma Method and Failure Mode and Effect Analysis (FMEA) - Oxamudra, Levana; Noya, Sunday; Ekawati, Yurida; Putrianto, Novenda Kartika; Oktiarso, Teguh; Purnomo, Purnomo (Teknik Industri Universitas Ma Chung, 2025)
PT XYZ is a manufacturing company producing cosmetic products, including 180 ml lotion packaged in tubes. Production data from January to July 2024 indicate an average defect rate of 0.82%, exceeding the company’s maximum tolerance limit of 0.8%. This study aims to evaluate process performance using the sigma level, identify the root causes of packaging defects, and propose effective quality improvement measures. The research employs the Six Sigma methodology integrated with Failure Mode and Effect Analysis (FMEA) through the DMAIC (Define, Measure, Analyze, Improve, and Control) framework. The results identify four dominant defect types: unsealed sealing, damaged caps, damaged batches, and dented containers. The initial process performance shows an average sigma level of 3.27, indicating suboptimal quality conditions. FMEA results reveal that the primary causes of defects are worn machine components, imprecise dosing and sealing mechanisms, and the absence of standardized work instructions. Improvement actions include replacing critical machine components, optimizing machine parameters, implementing bulk material viscosity control, and installing a leakage tester. Post-implementation evaluation demonstrates a significant improvement in quality performance, with the sigma level increasing to 4.30 and the average defect rate decreasing by 96.65%. These findings confirm that the integration of Six Sigma and FMEA is effective in reducing packaging defects and enhancing process stability in cosmetic manufacturing.